Quantitative trait loci associated with apple endophytes during pathogen infection - Karlström, Amanda; Papp-Rupar, Matevz; Passey, Tom A. J.; Deakin, Greg; Xu, Xiangming (Frontiers in Plant Science, 2023)
The phyllosphere microbiome has been linked to many aspects of plant fitness, including host resilience to plant pathogens. The assemblages of bacterial and fungal endophytes are shaped by multiple factors, including environment but also host genotype. In this work, the genetic basis of bacterial and fungal endophyte abundance was studied in a full-sibling family of apple (Malus x domestica) trees infected with Neonectria ditissima, a major fungal pathogen of apple. A Quantitative Trait Loci (QTL) analysis shows that multiple loci affect the abundance of specific endophytic taxa and suggest that certain loci can influence more than one group of microorganisms. Only a small proportion of the variation in overall taxonomic composition was affected by host genotype, with significant QTL hits for principal components explaining <8% and <7.4% of the total variance in bacterial and fungal composition, respectively. Four of the identified QTL colocalised with previously identified regions associated with tolerance to European canker. These results suggest that there is a genetic basis shaping apple endophyte composition and that microbe-host associations in apple could be tailored through breeding.